Mengkaji Nilai-Nilai Pendidikan Agama Islam Dalam Ritual Bersih Desa Di Desa Wringinanom Kecamatan Sambit Kabupaten Ponorogo - Muhammad Umbar Miftahuddin; Muhammad Aris Umami; Ahmad Syariful Burhan (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The village clean ritual in Wringinanom Village, Sambit District, Ponorogo Regency is carried out in a place that is considered sacred by the Wringinanom community. This study aims to provide an understanding to the community that the village clean ritual has Islamic religious educational values, because there are still many people who think that the village clean ritual is an act of shirk and associating partners with God. The method that the researcher uses is a qualitative method where the researcher tries to explain, describe, and describe which aims to collect data and information in order to solve these problems. There are four values ​​of Islamic religious education in the village clean ritual in Wringinanom Village. First, the value of monotheism or aqidah in the form of the belief of the Wringinanom Village community towards Allah swt who has given everything and only to Allah they ask for everything. Second, the value of worship in the form of activities in village clean rituals such as praying together, istigosah, dhikr together and sholawatan. Third, moral values ​​in the form of shodaqoh activities and the attitude of community responsibility in village clean rituals. Fourth, social values ​​where the villagers of Wringinanom uphold the attitude of getting along in harmony, mutual cooperation and mutual cooperation in implementing and preserving the village clean ritual in Wringinanom village. The values ​​of Islamic religious education in village clean rituals are able to provide benefits to the community and teach the community how to be grateful.